Cervicovaginal bacterial count and failure of metronidazole therapy for bacterial vaginosis - Luchiari, Heloise R. [UNESP]; Ferreira, Carolina S.T. [UNESP]; Golim, Márjorie A. [UNESP]; Silva, Márcia G. [UNESP]; Marconi, Camila (My University, 2016)
Objective To evaluate whether total bacterial count in cervicovaginal fluid is associated with failure of metronidazole therapy for bacterial vaginosis. Methods In a cross-sectional study, women attending a primary health center in Botucatu, São Paulo, Brazil, for routine cervical screening between September 2012 and October 2013 were enrolled. Women who tested positive for bacterial vaginosis (Nugent classification) were offered oral metronidazole. Women who completed metronidazole treatment and an equal number of control women with normal vaginal flora at initial screening were included in analyses of total bacterial count, assessed by flow cytometry of cervicovaginal fluid samples. Results Of 287 women who enrolled, 49 were excluded because they tested positive for trichomoniasis, chlamydial endocervicitis, gonorrhea, or candidiasis. Among the remaining 238, 85 (35.7%) had bacterial vaginosis. Among 36 women evaluated at follow-up, 23 (63.9%) had successfully restored lactobacilli-dominant flora, 12 (33.3%) had persistent bacterial vaginosis, and 1 (2.8%) had vaginal candidiasis (excluded from flow cytometry). Total bacterial count did not differ between 35 women with bacterial vaginosis and 35 with normal vaginal flora (P = 0.62). Total bacterial count did not differ at enrollment between women who went on to have persistent bacterial vaginosis and those who had successful treatment (P = 0.78). Conclusion Failure of oral metronidazole therapy for bacterial vaginosis was not associated with total bacterial count in cervicovaginal fluid.
Keywords: Bacterial vaginosis; Flow cytometry; Metronidazole; Total bacterial count